From fisher tales to scientific evidence: revealing the significance of estuarine and mangrove habitats as nursery grounds for juveniles of the largest Atlantic Ocean snapper - da Silva, Fábio Renan Miranda; Noleto Filho, Eurico Mesquita; Gallina, Maria Luiza; Keppeler, Friedrich Wolfgang; Loiola, Miguel; Giarrizzo, Tommaso; Reis-Filho, José Amorim (Frontiers in Marine Science, 2023)
The knowledge held by local and indigenous communities has been recognized as an invaluable yet underused resource for understanding how the environment, local conditions, and fish populations change over time. Empirical information on population sizes, ecology, and threats to fish species and their habitats can be complemented with local knowledge to better guide management and conservation efforts, particularly for understudied species. Here, we investigated the habitat preferences, population status, fishing, sightings patterns, threats, and habitat characteristics of juveniles of the cubera snapper, the largest snapper in the Atlantic Ocean. We used a combination of empirical evidence from underwater surveys by using small-action cameras and an ethnological perspective based on fishers’ perceptions who are cubera-snapper fishing specialists to have a comprehensive understanding of the species and habitat use during its early life stages. A range of estuarine habitats was examined over a year to assess the association between cubera snapper juveniles and different estuarine characteristics and conservation scenarios. Both sources of data indicated that cubera snapper juveniles heavily rely on mangrove habitats, exhibiting a clear temporal pattern of residence within these habitats. However, the probability of occurrence varied based on the level of coastal development in each estuarine system. Estuaries with small drainage areas, directly connected to the ocean, and presenting larger mangrove areas accounted for the highest abundances of juveniles. Factors such as mangrove removal, overfishing, and water pollution significantly reduced the occurrence and reliance of cubera snapper juveniles in the studied estuaries. The study represents the first attempt to shed light on the ecological aspects of cubera snapper juveniles, addressing a gap in their life cycle. It underscores the importance of integrating complementary sources of evidence to understand the relationships between the crucial life stage of cubera snappers, their habitats, and the threats they face. The ecological and ethnographic knowledge gained from this research should be incorporated into biomonitoring and conservation policy to effectively preserve this vulnerable top predator.